Flood planning: The politics of water security - Warner, Jeroen (London I.B. Tauris & Co. Ltd., 2011)
Floods are amongst the most common and devastating natural disasters. In the wake of such an event, the pressure to initiate flood protection schemes that will provide security is enormous, and politicians promise quick solutions in the national interest. Jeroen Warner examines a number of such projects from around the world - the Middle East, South Asia and Western Europe - aimed at the prevention of serious flooding.